2008
DOI: 10.1007/s10549-008-0132-0
|View full text |Cite
|
Sign up to set email alerts
|

The Austrian fulvestrant registry: results from a prospective observation of fulvestrant in postmenopausal patients with metastatic breast cancer

Abstract: International audienceEndocrine therapy is the preferred treatment in oestrogen- and/or progesterone-receptor (ER/PgR) positive breast cancer. Fulvestrant is a pure ER-antagonist. We present results from the Austrian Fulvestrant Registry. Three-hundred and fifty patients were included. Time to progression (TTP) was defined as primary endpoint. A multivariate analysis was performed to identify factors significantly associated with TTP. Fulvestrant was administered as first-line therapy in 26%, second-line in 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In phase III clinical trials, treatment with fulvestrant has been observed to result in a clinical benefit rate (i.e., complete response, partial response, and stable disease C24 weeks) of 54.3% in the first-line metastatic setting [6], and between 32.2 and 44.6% for subsequent lines of therapy [7][8][9]. Additionally, phase IV studies involving the review of compassionate use databases and including over 1,100 patients have observed clinical benefit rates of approximately 37% [10][11][12][13][14][15][16]. In these trials, the study population was quite heterogeneous, and complete clinical information was not available for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…In phase III clinical trials, treatment with fulvestrant has been observed to result in a clinical benefit rate (i.e., complete response, partial response, and stable disease C24 weeks) of 54.3% in the first-line metastatic setting [6], and between 32.2 and 44.6% for subsequent lines of therapy [7][8][9]. Additionally, phase IV studies involving the review of compassionate use databases and including over 1,100 patients have observed clinical benefit rates of approximately 37% [10][11][12][13][14][15][16]. In these trials, the study population was quite heterogeneous, and complete clinical information was not available for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that TTP was significantly higher for fulvestrant when compared to anastrozole (median TTP not reached for fulvestrant against 12.5 months for anastrozole (P = 0.0496). Ingle et al [14] observed a TTP of 3 months, whereas Mlineritsch et al [15] observed a median TTP of 6.4 months and Bartsch et al [9] of 7 months, all of them while studying postmenopausal women with metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant has been studied as both first-and secondline therapy for locally advanced and metastatic breast cancer, but few studies [8][9][10] exist showing its effect as third-line therapy alone. In this study, we correlated the disease time to progression (TTP) obtained with fulvestrant when used on metastatic breast cancer as first-, second-, and also third-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In phase III trials, fulvestrant was active and well-tolerated in patients who failed tamoxifen [24] or non-steroidal AI therapy [25,26], and is recommended in the second-line setting by clinical guidelines [5,6]. Recent evidence also indicates that fulvestrant may be useful in the first-line setting [27]. Ongoing trials will help to elucidate the full potential of this agent in patients with MBC.…”
Section: Endocrine Therapy For Mbcmentioning
confidence: 99%